Conductive binder and preparation method thereof
By grafting the adhesive on the surface of the conductive agent of the lithium-ion battery and copolymerizing with other monomers to form a conductive adhesive, the problem of difficult dispersion of the conductive agent in the negative electrode system is solved, and the electrochemical performance and cycle life of the battery are improved.
Patent Information
- Application Number
- CN202311327226.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-13
- Publication Date
- 2025-04-15
AI Technical Summary
The conductive agents of existing lithium-ion batteries are difficult to disperse in the negative electrode system, resulting in poor wetting and poor electrochemical performance.
By grafting the adhesive on the surface of the conductive agent, a modified conductive agent is formed, and copolymerized with acrylic acid, alkenyl polyether monomer, bonding monomer and crosslinking monomer to form a conductive adhesive with good dispersion and conductivity.
It improves the dispersion and electrochemical properties of the conductive agent, enhances the cycle life and rate performance of the battery, and reduces the processing time and the dosage of additives in the previous process.
Smart Images

Figure BDA0004492916560000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to a lithium-supplementing composite conductive agent for lithium-ion batteries and a preparation method thereof. Background Art
[0002] Since its development, lithium-ion batteries have been widely used in electronic consumer products, electric vehicles and energy storage due to their high energy density, no memory effect, long cycle life and other advantages. Nowadays, fast charging capability, low temperature performance and safety performance are important bottlenecks for the further development of lithium-ion batteries.
[0003] Conductive agents can provide channels for electron transmission in batteries, which is beneficial to the cycle life and rate performance of batteries. However, they are small in particle size and large in specific surface area, making them difficult to disperse. Especially in the negative electrode system, their strong lipophilicity leads to poor wetting. They rely on CMC thickeners and high-speed shearing for dispersion, which increases the time and risk required for the previous process and easily affects the slurry dispersion effect and coating quality. The widely used PAA binder is highly hydrophilic and has poor affinity with the conductive agent. It is difficult to form a uniform conductive network on the surface of the active material. However, PAA has a large synthetic modification space and has good dispersion performance. Based on these characteristics, a PAA binder can be developed by chemically grafting the conductive agent. The conductive agent can be dispersed in the PAA binder and can undergo grafting and cross-linking reactions at room temperature. On the one hand, it improves the processing efficiency of the previous process, and on the other hand, it can form a more uniform conductive film with PAA on the active material to enhance the electrochemical performance. Summary of the invention
[0004] Based on this, one of the purposes of the present invention is to provide a conductive adhesive to address the deficiencies of the prior art, by grafting the adhesive on the surface of the conductive agent to enable the conductive adhesive to have good dispersibility and conductivity, thereby enhancing the electrochemical performance of the battery.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] A conductive adhesive, wherein the raw materials used to prepare the conductive agent in the conductive adhesive include a surface-modified conductive agent, and the raw materials used to prepare the binder in the conductive adhesive include acrylic acid, alkenyl polyether monomers, bonding monomers, and crosslinking monomers. The conductive agent and the binder are grafted into the conductive adhesive.
[0007] The conductive adhesive of the present invention is prepared by modifying the surface of a conductive agent to obtain a modified conductive agent, and then copolymerizing an acrylic monomer, an alkenyl polyether monomer, a bonding monomer and a cross-linking monomer. The emulsion after the reaction is grafted with the modified conductive agent to connect the conductive agent and the adhesive through the modified molecules, thereby achieving the modified adhesive having uniform dispersion and good conductive properties, thereby improving the electrochemical properties of the battery.
[0008] Further, the surface modified conductive agent is amino group modified or hydroxyl group modified or carboxyl group modified, and further, the modified group also includes Na + , Li + NH4 + The conductive agent in the surface-modified conductive agent is one or more of single-arm carbon nanotubes, multi-arm carbon nanotubes, conductive carbon black, conductive graphite, vapor-grown carbon fiber, and graphene.
[0009] Furthermore, the alkenyl polyether monomer includes one or more of isobutylene alcohol polyoxyethylene ether, alkylene alcohol polyoxyethylene ether, isopentanol polyoxyethylene ether, hydroxybutyl vinyl polyoxyethylene ether, allyl polyoxyethylene ether, methyl alkenyl polyoxyethylene ether, and ethylene glycol monovinyl polyoxyethylene ether.
[0010] Further, the bonding monomer includes one or more of acrylonitrile, acrylamide, ethyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, itaconic acid, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.
[0011] Further, the cross-linking monomer includes one or more of diacetone acrylamide, glycidyl methacrylate, N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, N-hydroxypropyl acrylamide, 3-isopropenyl-dimethylbenzyl isocyanate, acetoacetoxy ethyl methacrylate, and acrylamidohydroxyacetic acid methyl ether.
[0012] Another object of the present invention is to provide a method for preparing a conductive adhesive, wherein a conductive adhesive having good electrochemical properties is obtained by solution polymerization of monomers followed by grafting reaction with a conductive agent.
[0013] In order to achieve the above object, the present invention adopts the following technical solutions:
[0014] A method for preparing a conductive adhesive, the method comprising the following steps:
[0015] S1. preparing a first emulsion and a second emulsion, wherein the first emulsion and the second emulsion include ionized water, acrylic acid, an alkenyl polyether monomer, a bonding monomer and a cross-linking monomer, and the mass ratio of the monomers in the first emulsion and the second emulsion is 1:1 to 10;
[0016] S2. In the first emulsion, the temperature is raised to 55°C to 85°C under an inert atmosphere, an initiator is added, and the second emulsion is added dropwise. After the addition is completed, the reaction is carried out for 1 to 3 hours to obtain a third emulsion;
[0017] S3. Mix and disperse the surface-modified conductive agent and the third emulsion, and add an alkaline solution to neutralize the mixture after dispersion to obtain the conductive adhesive.
[0018] Specifically, the second emulsion is added dropwise for 2 to 4 hours.
[0019] Specifically, the initiator is one or more of potassium persulfate, sodium persulfate, and ammonium persulfate, and the mass ratio of the initiator to the monomer is 1 to 10:1000.
[0020] Another object of the present invention is to provide a battery negative electrode, comprising the above-mentioned conductive binder.
[0021] In order to achieve the above object, the present invention adopts the following technical solutions:
[0022] A negative electrode for a lithium-ion battery comprises a current collector and a positive electrode active coating arranged on the surface of the current collector, wherein the negative electrode is coated with the conductive adhesive mentioned above.
[0023] Another object of the present invention is to provide a lithium ion battery, comprising the above-mentioned battery negative electrode material.
[0024] In order to achieve the above object, the present invention adopts the following technical solutions:
[0025] A lithium ion battery comprises the lithium ion negative electrode material described above.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] (1) The conductive agent with active groups after surface treatment is dispersed into the PAA binder, and the PAA end undergoes a grafting reaction with the active groups, which can reduce the processing time of the conductive agent in the previous process and the amount of additives used, thereby improving the slurry coating effect.
[0028] (2) The conductive agent can be filled into the PAA adhesive through chemical grafting and cross-linking to enhance the bonding performance and film cohesion and improve the cycle performance.
[0029] (3) The conductive agent is chemically grafted during the film formation process. Compared with the ordinary physical coating and bonding effect, covalent bond cross-linking can provide better stability and build a more uniform conductive network, thereby improving the electrochemical performance. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.
[0031] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0032] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0033] Example 1
[0034] 1. Preparation of modified conductive agent
[0035] Weigh 40g of carbon nanotubes acidified with mixed acid (concentrated nitric acid and concentrated sulfuric acid), reflux with 500ml of ethylenediamine and 20g of DCC (dicyclohexylcarbodiimide) at 100°C for 24h to modify the carbon nanotubes with amino groups, clean them with anhydrous ethanol ultrasonically and filter them to obtain an activated modified conductive agent.
[0036] 2. Preparation of Binder
[0037] (1) Preparation of the first emulsion
[0038] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of isobutylene alcohol polyoxyethylene ether, 3 parts of acrylonitrile, and 2 parts of diacetone acrylamide were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 60°C by water bath heating, and the speed of the stirrer was controlled to 50 rpm. When the temperature was 60°C, potassium persulfate as an initiator was added.
[0039] (2) Preparation of the second emulsion
[0040] According to the mass ratio, 420 parts of deionized water, 48 parts of acrylic acid, 12 parts of alkylene polyoxyethylene ether, 12 parts of acrylamide monomer, and 8 parts of glycidyl methacrylate (1:4) were taken and mixed evenly.
[0041] (3) Solution polymerization
[0042] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 60°C, the dropping speed was controlled, and the dropping time was 2 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 50 rpm. After reacting for 1 hour, the third emulsion was obtained by cooling.
[0043] 3. Dispersion and Neutralization
[0044] The third emulsion is mixed with the modified conductive agent, and the third emulsion and the modified conductive agent are dispersed by frosting. Finally, lithium hydroxide is added for neutralization to obtain a grafted conductive adhesive.
[0045] Example 2
[0046] 1. Preparation of modified conductive agent
[0047] Weigh 40 g of the mixed acid-modified conductive carbon black, use the conductive carbon black as a conductive agent, and reduce it at high temperature under a hydrogen atmosphere to obtain an activated modified conductive agent.
[0048] 2. Preparation of Binder
[0049] (1) Preparation of the first emulsion
[0050] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of isopentanol polyoxyethylene ether, 3 parts of ethyl acrylate, and 2 parts of N-hydroxymethyl acrylamide were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 65°C by water bath heating, and the speed of the stirrer was controlled to 100 rpm. When the temperature was 65°C, the initiator sodium persulfate was added.
[0051] (2) Preparation of the second emulsion
[0052] According to the mass ratio, 460 parts of deionized water, 24 parts of acrylic acid, 6 parts of hydroxybutyl vinyl polyoxyethylene ether monomer, 6 parts of 2-ethylhexyl acrylate, and 4 parts of N-hydroxyethyl acrylamide monomer were taken (1:2) and mixed evenly.
[0053] (3) Solution polymerization
[0054] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 65°C, the dropping speed was controlled, and the dropping time was 3 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 100 rpm. After reacting for 2 hours, the third emulsion was obtained by cooling.
[0055] 3. Dispersion and Neutralization
[0056] The third emulsion is mixed with the modified conductive agent, the third emulsion and the modified conductive agent are dispersed by ball milling, and finally sodium hydroxide is added for neutralization to obtain a grafted conductive adhesive.
[0057] Example 3
[0058] 1. Preparation of modified conductive agent
[0059] Weigh 40 g of conductive graphite, use the conductive graphite as a conductive agent, modify the conductive graphite with concentrated nitric acid and concentrated sulfuric acid, rinse with deionized water and ethanol, filter and separate, and obtain an activated modified conductive agent.
[0060] 2. Preparation of Binder
[0061] (1) Preparation of the first emulsion
[0062] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of allyl polyoxyethylene ether, 3 parts of methacrylic acid, and 2 parts of N-hydroxypropyl acrylamide were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 70°C by water bath heating, and the speed of the stirrer was controlled to 150 rpm. When the temperature was 70°C, the initiator ammonium persulfate was added.
[0063] (2) Preparation of the second emulsion
[0064] According to the mass ratio, 380 parts of deionized water, 72 parts of acrylic acid, 18 parts of methyl vinyl polyoxyethylene ether, 18 parts of itaconic acid, and 12 parts of 3-isopropenyl-dimethylbenzyl isocyanate (1:6) were taken and mixed evenly.
[0065] (3) Solution polymerization
[0066] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 70°C, the dropping speed was controlled, and the dropping time was 3 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 150 rpm. After reacting for 3 hours, the third emulsion was obtained by cooling.
[0067] 3. Dispersion and Neutralization
[0068] The third emulsion is mixed with the modified conductive agent, and the third emulsion and the modified conductive agent are dispersed by a high-speed dispersion method, and finally ammonia water is added for neutralization to obtain a grafted conductive adhesive.
[0069] Example 4
[0070] 1. Preparation of modified conductive agent
[0071] Weigh 20g of graphene oxide treated with mixed acid, use graphene oxide as a conductive agent, reflux react with 500ml of ethylenediamine and 20g of DCC (dicyclohexylcarbodiimide) to modify the graphene oxide, use anhydrous ethanol to ultrasonically clean it and then filter it to obtain an activated modified conductive agent.
[0072] 2. Preparation of Binder
[0073] (1) Preparation of the first emulsion
[0074] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of ethylene glycol monovinyl polyoxyethylene ether, 3 parts of 2-hydroxyethyl acrylate, and 2 parts of methyl benzyl isocyanate were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 80°C by heating in a water bath, and the speed of the agitator was controlled to 200 rpm. When the temperature was 80°C, potassium persulfate as an initiator was added.
[0075] (2) Preparation of the second emulsion
[0076] According to the mass ratio, 340 parts of deionized water, 96 parts of acrylic acid, 24 parts of ethylene glycol monovinyl polyoxyethylene ether, 24 parts of 2-hydroxypropyl acrylate, and 16 parts of ethyl acetoacetate methacrylate were taken (1:8) and mixed evenly.
[0077] (3) Solution polymerization
[0078] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 80°C, the dropping speed was controlled, and the dropping time was 2 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 200 rpm. After reacting for 2 hours, the third emulsion was obtained by cooling.
[0079] 3. Dispersion and Neutralization
[0080] The third emulsion is mixed with the modified conductive agent, and the third emulsion and the modified conductive agent are dispersed by frosting. Finally, lithium hydroxide is added for neutralization to obtain a grafted conductive adhesive.
[0081] Example 5
[0082] 1. Preparation of modified conductive agent
[0083] Weigh 40g of vapor-grown carbon fiber (VGCF) treated with mixed acid, use VGCF as a conductive agent, reflux react with 500ml of ethylenediamine and 20g of DCC (dicyclohexylcarbodiimide) to modify the VGCF, ultrasonically clean it with anhydrous ethanol and then filter it to obtain the activated modified conductive agent.
[0084] 2. Preparation of Binder
[0085] (1) Preparation of the first emulsion
[0086] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of isobutylene alcohol polyoxyethylene ether, 3 parts of acrylonitrile, and 2 parts of diacetone acrylamide were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 80°C by water bath heating, and the speed of the agitator was controlled to 200 rpm. When the temperature was 80°C, potassium persulfate as an initiator was added.
[0087] (2) Preparation of the second emulsion
[0088] According to the mass ratio, take 300 parts of deionized water, 120 parts of acrylic acid, 30 parts of isobutylene alcohol polyoxyethylene ether, 30 parts of acrylonitrile, and 20 parts of diacetone acrylamide (1:10), and mix them evenly.
[0089] (3) Solution polymerization
[0090] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 80°C, the dropping speed was controlled, and the dropping time was 2 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 200 rpm. After reacting for 2 hours, the third emulsion was obtained by cooling.
[0091] 3. Dispersion and Neutralization
[0092] The third emulsion is mixed with the modified conductive agent, and the third emulsion and the modified conductive agent are dispersed by frosting. Finally, lithium hydroxide is added for neutralization to obtain a grafted conductive adhesive.
[0093] Comparative Example 1
[0094] 1. Preparation of binder
[0095] (1) Preparation of the first emulsion
[0096] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of isobutylene alcohol polyoxyethylene ether, 3 parts of acrylonitrile, and 2 parts of diacetone acrylamide were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 60°C by water bath heating, and the speed of the stirrer was controlled to 50 rpm. When the temperature was 60°C, potassium persulfate as an initiator was added.
[0097] (2) Preparation of the second emulsion
[0098] According to the mass ratio, 420 parts of deionized water, 48 parts of acrylic acid, 12 parts of alkylene polyoxyethylene ether, 12 parts of acrylamide monomer, and 8 parts of glycidyl methacrylate (1:4) were taken and mixed evenly.
[0099] (3) Solution polymerization
[0100] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 60°C, the dropping speed was controlled, and the dropping time was 2 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 50 rpm. After reacting for 1 hour, the third emulsion was obtained by cooling.
[0101] 2. Dispersion and Neutralization
[0102] The third emulsion was mixed with 40 g of carbon nanotubes, and the third emulsion and the carbon nanotubes were dispersed by frosting. Finally, lithium hydroxide was added for neutralization to obtain a mixture of a conductive agent and a binder.
[0103] Comparative Example 2
[0104] 1. Preparation of binder
[0105] (1) Preparation of the first emulsion
[0106] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of allyl polyoxyethylene ether, 3 parts of methacrylic acid, and 2 parts of N-hydroxypropyl acrylamide were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 70°C by water bath heating, and the speed of the stirrer was controlled to 150 rpm. When the temperature was 70°C, the initiator ammonium persulfate was added.
[0107] (2) Preparation of the second emulsion
[0108] According to the mass ratio, 380 parts of deionized water, 72 parts of acrylic acid, 18 parts of methyl vinyl polyoxyethylene ether, 18 parts of itaconic acid, and 12 parts of 3-isopropenyl-dimethylbenzyl isocyanate (1:6) were taken and mixed evenly.
[0109] (3) Solution polymerization
[0110] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 70°C, the dropping speed was controlled, and the dropping time was 3 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 150 rpm. After reacting for 3 hours, the third emulsion was obtained by cooling.
[0111] 2. Dispersion and Neutralization
[0112] The third emulsion was mixed with 40 g of conductive graphite, and the third emulsion and the conductive graphite were dispersed by high-speed dispersion. Finally, ammonia water was added for neutralization to obtain a mixture of a conductive agent and a binder.
[0113] Comparative Example 3
[0114] 1. Preparation of binder
[0115] (1) Preparation of the first emulsion
[0116] According to the mass ratio, 480 parts of deionized water, 12 parts of acrylic acid, 3 parts of ethylene glycol monovinyl polyoxyethylene ether, 3 parts of 2-hydroxyethyl acrylate, and 2 parts of methyl benzyl isocyanate were added to a round-bottom flask and stirred to prepare S1 solution. Nitrogen was introduced to maintain an inert atmosphere. The reaction temperature of the S1 solution was raised to 80°C by heating in a water bath, and the speed of the agitator was controlled to 200 rpm. When the temperature was 80°C, potassium persulfate as an initiator was added.
[0117] (2) Preparation of the second emulsion
[0118] According to the mass ratio, 340 parts of deionized water, 96 parts of acrylic acid, 24 parts of ethylene glycol monovinyl polyoxyethylene ether, 24 parts of 2-hydroxypropyl acrylate, and 16 parts of ethyl acetoacetate methacrylate were taken (1:8) and mixed evenly.
[0119] (3) Solution polymerization
[0120] The second emulsion was added dropwise to the first emulsion, the reaction temperature was maintained at 80°C, the dropping speed was controlled, and the dropping time was 2 hours. After the second emulsion was completely added dropwise, the speed of the agitator was controlled to 200 rpm. After reacting for 2 hours, the third emulsion was obtained by cooling.
[0121] 2. Dispersion and Neutralization
[0122] The third emulsion was mixed with 20 g of graphene, and the third emulsion and graphene were dispersed by frosting. Finally, lithium hydroxide was added for neutralization to obtain a mixture of a conductive agent and a binder.
[0123] The conductive binder prepared in Examples 1-5 of the present invention and Comparative Examples 1-3 is a negative electrode material, which is evenly mixed in a mass ratio of graphite: conductive binder = 96:4 to prepare a negative electrode slurry, and the obtained negative electrode slurry is coated on a copper foil current collector; the positive electrode slurry is evenly mixed in a mass ratio of lithium iron phosphate: PVDF: conductive agent = 96:2:2 to prepare a positive electrode slurry, and the obtained positive electrode slurry is coated on an aluminum foil current collector. After drying and rolling, a negative electrode sheet and a positive electrode sheet are obtained, and the negative electrode sheet, the positive electrode sheet, the separator, and the electrolyte are assembled into a 2025 button battery.
[0124] The manufactured battery and negative electrode were tested. See Table 1 for the test data.
[0125] The button cells prepared in Examples 1-5 and Comparative Examples 1-3 of the present invention were subjected to discharge capacity tests: The discharge capacity tests were conducted in a blue electric test system, and the charge and discharge conditions were set as follows: (1) charging at 0.1C to a cut-off voltage of 3.7V, discharging to a cut-off voltage of 2.5V, and cycling for 5 cycles; (2) charging at 4C to a cut-off voltage of 3.7V, discharging to a cut-off voltage of 2.5V, and cycling for 5 cycles. The test data are shown in Table 1.
[0126] Table 1 Performance test results of samples prepared in Examples 1-5 and Comparative Examples 1-3
[0127]
[0128] The main difference between Example 1, Example 2, Example 3, Example 4 and Example 5 of the present invention is that in the process of preparing the conductive adhesive, the activation modification method used for the conductive agent raw material is different, and the ratio of the adhesive raw material is also different. It can be seen from the chart that the resistivity of the conductive film of the battery pole piece made by the conductive adhesive of Example 1, Example 2, Example 3, Example 4 and Example 5 is much lower than that of the battery pole piece made by the adhesive of Comparative Example 1, Comparative Example 2 and Comparative Example 3. Although there is a slight difference in the resistivity of the battery conductive film of Example 1, Example 2, Example 3, Example 4 and Example 5, the possible reason is that different conductive agents are modified and activated in different ways. Generally speaking, the difference is not big.
[0129] Combining the 0.1C and 4C discharge capacities of the batteries in the chart, it can be concluded that the discharge capacities of the batteries prepared in Example 1, Example 2, Example 3, Example 4 and Example 5 are higher than those in Comparative Example 1, Comparative Example 2 and Comparative Example 3, while the 0.1C and 4C discharge capacities of the conductive agents modified in different ways are not much different. This indicates that in the process of preparing the conductive adhesive, after the conductive agent is activated and modified, the conductivity of the conductive film can be significantly reduced, and the electrical performance of the battery prepared by the treated conductive agent is better.
[0130] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.
Claims
1. A conductive adhesive, characterized in that: The raw materials for preparing the conductive agent in the conductive adhesive include surface-modified conductive agent, and the raw materials for preparing the binder in the conductive adhesive include acrylic acid, alkenyl polyether monomers, bonding monomers, and crosslinking monomers. The conductive agent and the binder are grafted into the conductive adhesive.
2. The conductive adhesive according to claim 1, characterized in that: The surface modified conductive agent is amino group modified, hydroxyl group modified or carboxyl group modified, and the conductive agent in the surface modified conductive agent is one or more of single-arm carbon nanotubes, multi-arm carbon nanotubes, conductive carbon black, conductive graphite, vapor-grown carbon fiber and graphene.
3. The conductive adhesive according to claim 1, characterized in that: The alkenyl polyether monomers include one or more of isobutylene alcohol polyoxyethylene ether, alkylene alcohol polyoxyethylene ether, isopentanol polyoxyethylene ether, hydroxybutyl vinyl polyoxyethylene ether, allyl polyoxyethylene ether, methyl alkenyl polyoxyethylene ether, and ethylene glycol monovinyl polyoxyethylene ether.
4. The conductive adhesive according to claim 1, characterized in that: The bonding monomer includes one or more of acrylonitrile, acrylamide, ethyl acrylate, 2-ethylhexyl acrylate, methacrylic acid, itaconic acid, 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, and 2-hydroxypropyl methacrylate.
5. The conductive adhesive according to claim 1, characterized in that: The cross-linking monomer includes one or more of diacetone acrylamide, glycidyl methacrylate, N-hydroxymethyl acrylamide, N-hydroxyethyl acrylamide, N-hydroxypropyl acrylamide, 3-isopropenyl-dimethylbenzyl isocyanate, acetoacetoxyethyl methacrylate, and acrylamidohydroxyacetic acid methyl ether.
6. The method for preparing a conductive adhesive according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: S1. preparing a first emulsion and a second emulsion, wherein the first emulsion and the second emulsion include ionized water, acrylic acid, an alkenyl polyether monomer, a bonding monomer and a cross-linking monomer, and the mass ratio of the monomers in the first emulsion and the second emulsion is 1:1 to 10; S2. In the first emulsion, the temperature is raised to 55°C to 85°C under an inert atmosphere, an initiator is added, and the second emulsion is added dropwise. After the addition is completed, the reaction is carried out for 1 to 3 hours to obtain a third emulsion; S3. Mix and disperse the surface-modified conductive agent and the third emulsion, and add an alkaline solution to neutralize the mixture after dispersion to obtain the conductive adhesive.
7. The method for preparing a conductive adhesive according to claim 6, characterized in that: The second emulsion is added dropwise for 2 to 4 hours.
8. The method for preparing a conductive adhesive according to claim 6, characterized in that: The initiator is one or more of potassium persulfate, sodium persulfate, and ammonium persulfate, and the mass ratio of the initiator to the monomer is 1 to 10:1000.
9. A negative electrode for a lithium ion battery, characterized in that: The negative electrode of the lithium-ion battery comprises a current collector and a positive electrode active coating disposed on the surface of the current collector, and the negative electrode coating comprises the conductive adhesive as claimed in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the lithium-ion negative electrode material as claimed in claim 9.